Comparative study of synthetic peptides corresponding to region 115-129 in Lys49 myotoxic phospholipases A2 from snake venoms - Lomonte, Bruno (2003)
Lys49 phospholipase A2 homologues constitute a group of catalytically-inactive proteins, present in the venoms of many crotalid snakes, which induce myonecrosis. Current evidence supports the mapping of their toxic site to the C-terminal region, where amino acids comprised within the sequence 115–129 appear to play a central role in toxicity. This study evaluated the possible toxic effects of several synthetic peptides corresponding to the sequence 115–129 of different Lys49 myotoxins, using in vitro cytotoxicity and in vivo myotoxicity assays. Peptides varied widely in their activities, ranging from fully toxic to harmless. Thus, the toxic actions of Lys49 myotoxins cannot always be reproduced by their free peptides 115–129. Peptides from Agkistrodon p. piscivorus (AppK) and A. contortrix laticinctus Lys49 myotoxins exerted both cytotoxicity and myotoxicity. Random scrambling of peptide AppK resulted in complete loss of toxicity, demonstrating that its specific sequence of residues, rather than their simple presence or frequency, confers its ability to damage muscle. Peptide AppK synthesized with D-amino acids retained both activities of the natural L-enantiomer, suggesting that its mechanism of action does not involve the recognition of a proteic receptor/acceptor site on muscle cells, but possibly the binding to other structures, such as negatively-charged membrane phospholipids.